Construction of retaining wall for the environmental perspective - Adi Saffuan Ahmad (Penerbit Universiti Malaysia Perlis, 2011)
This study aimed to identify the type of retaining wall, retaining wall construction method and environmental point of view as well as modification of the panel can be updated to meet the aesthetic values. Construction of retaining walls is different in each project. The project is meant Electrified Double Track Project. Construction of retaining wall at the project site at Jalan Sultanah the Wall Nehemiah Nehemiah wall for which this is the kind of Anchored Wall. Thus, construction of retaining wall must be in accordance with the view that this environment does not have an adverse impact on the environment. A study on air quality, noise and vibration are also considered. Retaining wall is a structure used to hold direct pressure from the outside and inside the wall itself. Retaining wall must be able to withstand the external pressure exerted on the ground. This external pressure has a tendency to lead to soil structure and failed to slip. In addition, to meet the aesthetic values of the wall panel structure of Nehemiah wall can be updated as colors, or pictures on the wall.